2017
DOI: 10.1021/acsnano.7b02943
|View full text |Cite
|
Sign up to set email alerts
|

How the Toughest Inorganic Fullerene Cages Absorb Shockwave Pressures in a Protective Nanocomposite: Experimental Evidence from Two In Situ Investigations

Abstract: Nanocomposites fabricated using the toughest caged inorganic fullerene WS (IF-WS) nanoparticles could offer ultimate protection via absorbing shockwaves; however, if the IF-WS nanomaterials really work, how they behave and what they experience within the nanocomposites at the right moment of impact have never been investigated effectively, due to the limitations of existing investigation techniques that are unable to elucidate the true characteristics of high-speed impacts in composites. We first fabricated Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Mechanical effects under transient loads have been investigated only scarcely. Probably, the most striking observation was recently reported, 160 whereby a projectile with a speed of some 1000 m/s hit an aluminum foil target filled with IF-WS 2 nanoparticles. The authors found that the presence of IF-WS 2 in the foil led to a moderation of the impact velocity by over 100 m/s and reduced the transient pressure by at least 2 GPa compared with the reference (Al foil loaded with WS 2 platelets).…”
Section: Tribological Characterizationmentioning
confidence: 92%
“…Mechanical effects under transient loads have been investigated only scarcely. Probably, the most striking observation was recently reported, 160 whereby a projectile with a speed of some 1000 m/s hit an aluminum foil target filled with IF-WS 2 nanoparticles. The authors found that the presence of IF-WS 2 in the foil led to a moderation of the impact velocity by over 100 m/s and reduced the transient pressure by at least 2 GPa compared with the reference (Al foil loaded with WS 2 platelets).…”
Section: Tribological Characterizationmentioning
confidence: 92%
“…J. H. Appel et al . reported on the interactions of naked MoS 2 nanosheets, obtained by mechanical exfoliation and chemical vapor deposition, with human epithelial kidney cells (HEK293f) observing low cytotoxicity and genotoxicity in their experimental conditions 38 . P. Shah et al .…”
Section: Introductionmentioning
confidence: 99%
“…Concentration dependent studies of MoS 2 nanosheets with Escherichia coli 44 , Bacillus subtilis and Staphylococcus aureus 42 revealed a decrease in the bacterial survival rate with increase in dispersion concentration. On the other hand, Salmonella typhimurium (S. typhimurium) , a discretionary gastric pathogen which is responsible for food poisoning in humans resulting in gastroentertitis 45 and represents a very dangerous gram negative bacterium, was studied only quite recently until now in its interaction with bare MoS 2 nanosheets 38 , 42 , 46 48 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve additional reinforcement of ballistic composite systems new technologies are developed. One of the ways to enhance protective performance of these composites is to add nanofillers of different properties and structures and tungsten disulfide is among them [36][37][38][39].…”
Section: Nanoreinforced Composites For Ballistic Protectionmentioning
confidence: 99%